Stranger things. Season 2 [videorecording (DVD)] - Ryder, Winona, 1971-; Harbour, David, 1975-; Wolfhard, Finn, 2002-; Brown, Millie Bobby, 2004-; Reiser, Paul (Netflix, 2018)
When a young boy vanishes, a small town uncovers a mystery involving secret experiments, terrifying supernatural forces and one strange little girl. It's 1984 and the citizens of Hawkins, Indiana are still reeling from the horrors of the demagorgon and the secrets of Hawkins Lab. Will Byers has been rescued from the Upside Down but a bigger, sinister entity still threatens those who survived.